Job satisfaction and family happiness: the part-time work puzzle - Alison L. Booth; Jan C. van Ours (University of Essex, Institute for Social and Economic Research (ISER), 2007)
Using fixed effects ordered logit estimation, we investigate the relationship between part-time work and working hours satisfaction; job satisfaction; and life satisfaction. We account for interdependence within the family using data on partnered men and women from the British Household Panel Survey. We find that men have the highest hours-of-work satisfaction if they work full-time without overtime hours but neither their job satisfaction nor their life satisfaction are affected by how many hours they work. Life satisfaction is influenced only by whether or not they have a job. For women we are confronted with a puzzle. Hours satisfaction and job satisfaction indicate that women prefer part-time jobs irrespective of whether these are small or large. In contrast, female life satisfaction is virtually unaffected by hours of work. Women without children do not care about their hours of work at all, while women with children are significantly happier if they have a job regardless of how many hours it entails.
Keywords: 330